Seasonal variation of water quality and waste loads in Buriganga river with GIS visualization - Alam, MK; Uddin, MA; Satter, MF; Majed, N (Bangladesh Journal of Scientific and Industrial Research, 2020)
Pollution status of the Buriganga river has been assessed in this study using GIS tool to analyze the spatial and seasonal distribution of several water quality parameters from six surface water sampling stations. In addition, characterization of water quality from certain selected outfalls discharging wastewater along the river was accomplished as well. The observed surface water quality concentration was higher during dry season for BOD5 (13.68-22.8 mg/l), COD (22-30 mg/l), TDS (280- 303 mg/l), PO4(5.6- 7.3 mg/l) while an exception was found for NH3-N (0.67- 0.89 mg/l) and Turbidity (25.19 to 91.18). The DO level was found noticeably lower during dry season (1.73 to 2.36 mg/l) than wet season (3.27 to 4.68 mg/l). Moreover, Principal Component Analysis identified high ionic distributions during wet season and more organic pollution during dry season. Water quality parameters TDS, TSS, EC and COD were obtained in high concentration levels from industrial outfalls towards the downstream of the river while BOD5, NH3-N were higher from municipal wastewater outfalls towards the upstream of the river. The observed pollution loading from the outfalls revealed the location at Dholaikhal as the major pollution source in the river with a BOD5 (11681- 12243 kg/day) and TDS (9749- 32348 kg/day) loading. Accordingly, influence of nearest wastewater sources on the surface water quality was evident through GIS representation of the parameters. Bangladesh J. Sci. Ind. Res.55(2), 113-130, 2020